PROFIL PENGELOLAAN VAKSIN COVID-19 DI RUMAH SAKIT UMUM PUSAT (RSUP) FATMAWATI JAKARTA - Kusuma, Rano (Jurnal Farmasi Klinik Best Practice, 2023)
Covid-19 has been a pandemic that has caused numerous casualties over the past three years. The government's efforts to reduce the outbreak and loss of life involve implementing vaccination for the public. Vaccines are biological products that are highly sensitive and easily damaged, thus requiring special handling in their management. RSUP Fatmawati is the main hospital in South Jakarta that carries out Covid-19 vaccinations. Good vaccines are also based on good management. This study aims to examine the management profile of Covid-19 vaccines in accordance with the management standards stated in the “Pedoman CDOB 2020” and “KMK No. HK.01.07-MENKES-4638-2021 tentang JUKNIS Pelaksanaan Vaksinasi Dalam Rangka Penanggulangan Pandemi Covid-19”. This research adopts a descriptive cross-sectional research method. Data collection is done prospectively using approaches such as direct observation or data collection. The results of the study indicate that the conformity of Covid-19 vaccine management with the sources obtained a score of 77.3%. The delivery indicator received a score of 75%, the storage indicator received a score of 75,6%, and the Covid-19 vaccine criteria indicator received a score of 71,4%. Meanwhile, the conformity with the “Pedoman CDOB 2020” obtained a score of 77.5%, and the “KMK No. HK.01.07-MENKES-4638-2021 tentang JUKNIS Pelaksanaan Vaksinasi Dalam Rangka Penanggulangan Pandemi Covid-19” received a score of 76,9%. Some aspects did not conform to the sources, such as the lack of supporting facilities such as humidity meters and malfunctioning temperature thermometers, lack of maintenance for equipment, and monitoring only being performed twice a day. It is recommended to pay attention to the condition and maintenance of the Covid-19 vaccine storage facilities, and temperature monitoring of the vaccines should be conducted at least three times a day.